IMPLEMENTASI PROGRAM SEKOLAH ADIWIYATA DALAM PENINGKATAN MUTU PENDIDIKAN DI SDN TANAH TINGGI 3 KOTA TANGERANG - Indah Kusuma Pradini; Bedjo Sudjanto; Nurjannah Nurjannah (Program Studi Manajemen Lingkungan, 2018)
This research was taken place in SDN Tanah Tinggi 3 Kota Tangerang with purpose to understanding the implementation of Adiwiyata school programs in enhancing education quality that is related to the policy of Adiwiyata school programs, the implementation of Adiwiyata school programs, supporting factors and obstacle factors of implementation of Adiwiyata school programs in SDN Tanah Tinggi 3 Kota Tangerang. The methodology that used is qualitative method with descriptive approach. Data collection procedure was conducted through observation, in-depth interview, and documentation. Source of data is headmaster, team head of Adiwiyata, member of Adiwiyata team, and teachers. Analysis conducted using data reduction, data presentation, and data verification. This research shows that the school successfully achieved an award as Adiwiyata Mandiri school by launching 12 adiwiyata programs including everyday without plastics, a simple IPAL management at school, healthy canteen, waste bank management, JUMSIH program (a clean Friday), compost management program, composter and 3R (reuse, reduce, and recycle), etc. The program was implemented according to a number of components such as environmentally based policy; implementation of environmentally based curriculum; environmental activities in participative basis and management of environmentally friendly supporting activities